How Do Changing U.S. Interest Rates Affect Banks in the Gulf Cooperation Council (GCC) Countries? - Adedeji, Olumuyiwa (IMF Working Papers; Working Paper ;, 2019)
Given their pegged exchange rate regimes, Gulf Cooperation Council (GCC) countries usually adjust their policy rates to match shifting U.S. monetary policy. This raises the important question of how changes in U.S. monetary policy affect banks in the GCC. We use bank-level panel data, exploiting variation across banks within countries, to isolate the impact of changing U.S. interest rates on GCC banks funding costs, asset rates, and profitability. We find stronger pass-through from U.S. monetary policy to liability rates than to asset rates and bank profitability, largely reflecting funding structures. In addition, we explore the role of shifts in the quantity of bank liabilities as policy rates change and the role of large banks with relatively stable funding costs to explain these findings.